Ibn Taymiyya on reason and revelation: a study of Dar' ta'arud al-'aql wa-l-naql - El-Tobgui, Carl Sharif (Islamic philosophy, theology and science, 2020)
Reason and revelation in islam before Ibn Taymiyya -- Ibn Taymiyya: life, times, and intellectual profile -- On the incoherence of the universal rule and the theoretical impossibility of a contradiction between reason and revelation -- Ṣaḥiḥ al-manqūl, or what is revelation? -- Ṣariḥ al-ma'qūl, or what is reason? -- Reason reconstituted: the divine attributes and the question of contradiction between reason and revelation.